2001
DOI: 10.1128/jb.183.3.1078-1084.2001
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Filament-Deficient Mutant of Treponema denticola Has Pleiotropic Defects

Abstract: In Treponema denticola, a ribbon-like structure of cytoplasmic filaments spans the cytoplasm at all stages of the cell division process. Insertional inactivation was used as a first step to determine the function of the cytoplasmic filaments. A suicide plasmid was constructed that contained part of cfpA and a nonpolar erythromycin resistance cassette (ermF and ermAM) inserted near the beginning of the gene. The plasmid was electroporated into T. denticola, and double-crossover recombinants which had the chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 53 publications
1
42
0
Order By: Relevance
“…Cytoplasmic filaments, formed by CfpA monomers (Izard et al, 2001), can be observed in both flagellate and aflagellate strains (Fig. 5).…”
Section: Cytoplasmic Filaments and Attachment Platementioning
confidence: 95%
See 2 more Smart Citations
“…Cytoplasmic filaments, formed by CfpA monomers (Izard et al, 2001), can be observed in both flagellate and aflagellate strains (Fig. 5).…”
Section: Cytoplasmic Filaments and Attachment Platementioning
confidence: 95%
“…The alignment of the cytoplasmic filaments and the flagellar filaments may be imposed by the overall geometry of the cells and mechanical constraints. Mutagenesis experiments indicated the absence of a relationship between those two structures (Izard et al, 2001). In a mutant strain lacking the cytoplasmic filament formed by CfpA proteins, the motility of single cells was not altered (Izard et al, 2001).…”
Section: Cytoplasmic Filaments and Attachment Platementioning
confidence: 97%
See 1 more Smart Citation
“…Cytoplasmic filaments are cytoplasmic structures located directly beneath the PF. A CfpA-deficient mutant displayed reduced spreading ability compared with wild-type strains, implicating involvement of cytoplasmic filaments in motility (Izard et al, 2001;Vesey and Kuramitsu, 2004).…”
Section: Periplasmic Flagellamentioning
confidence: 98%
“…Coiled coil rich proteins (e.g., CfpA) have also been described in the cork-screw like bacterial branch of the Spirochaetes, where a bundle of four to six cytoplasmatic filaments runs along the long axis of the long and thin cells [Izard, 2006]. CfpA is a major constituent of the structure-however, its loss affects the subcellular arrangement of the genome rather than cell shape [Izard et al, 2001]. Finally, AglZ is a coiled coil rich protein which forms filamentous structures in vitro, and is involved in motility in the Gram negative proteobacterium Myxococcus xanthus [Yang et al, 2004], which is famous for its social behaviour-cells aggregate on surfaces upon starvation and build fungus-like fruiting bodies.…”
Section: Coiled Coil Rich Proteinsmentioning
confidence: 99%